Potential of Using Shear Wave Elastography in the Clinical Evaluation and Monitoring of Changes in Masseter Muscle Stiffness - Cyprian Olchowy; Mieszko Więckiewicz; Luca Maria Sconfienza; Mateusz Łasecki; Piotr Seweryn; Joanna Smardz; Sylwia Hnitecka; Marzena Dominiak; Anna Olchowy (Pain Research and Management)
The study aimed to evaluate masseter muscle stiffness in adult healthy volunteers referred to a massage treatment and also to investigate whether shear-wave elastography can be used to monitor the effect of massage on the masseter muscle. The study included 21 healthy volunteers, who were subjected to a 30-minute massage of the masseter muscle. Muscle stiffness was measured by shear-wave elastography before and directly after the massage. Pain during the massage was assessed using the visual analogue scale (VAS). The data of 20 patients (one excluded due to severe pain) with a median age of 34.5 years were analysed. The stiffness values were 11.46 ± 1.55 kPa before and 8.97 ± 0.96 kPa after the massage (p<0.0001). The mean drop was 2.49 ± 1.09 kPa. The greatest decrease was observed in people with higher elasticity values before the massage (r = 0.79; p<0.0001). The median intensity of pain was 7.2 (range: 6–9.5). We concluded that shear-wave elastography is a sensitive tool to monitor changes in the stiffness of the masseter muscle.